Effects of Insecurity on the Profitability of Matatu Industry in Nairobi County (Impact: Journal of Transformation, 2022)
The study sought to determine the effect of violent, non-violent and gender-based violence insecurity on the matatu industry profitability in Nairobi County. The target population of the study was 197 Public Service Vehicles SACCOS registered in Nairobi in 2019. The study adopted an exploratory and descriptive research design. The study sought to shed light into the level of insecurity in the public transport and how insecurity affects the sector thus informing the appropriate measures that ought to be put in place to curb the menace. The study applied census given that the target population was small in size. Structured questionnaires with open-ended questions were used. A simple Ordinary Least Square regression model was applied to estimate the effect of violent, non-violent and gender-based violence insecurity on privately owned vans which travels a long a fixed route (matatu) industry profitability. From the study findings, nonviolent insecurities comprising of theft of passengers’ luggage and drugging have the highest negative effect on profitability. The study concludes that although gender-based insecurities negatively affect profitability of matatu industry in Nairobi County in Kenya, the magnitude of their effect is suppressed. The study recommends a multi-stakeholder approach to tackle insecurity in the matatu industry, the need for awareness creation and sensitization to the matatu owners on the need to enhance security in their areas of operations, efforts such as employing personal guards at the matatu terminals, installing matatus with security monitoring devices would go a long way in reducing such insecurity incidences in the industry. Fourthly, regulations by the National Transport Authority requiring matatu SACCOS to put up security measures and supervise adherence to these regulations and there is the need for national and county government to form a special security unit to deal with insecurity incidences within Nairobi Central Business District and the Nairobi metropolitan at large.